Biofabrication and Bone Tissue Regeneration: Cell Source, Approaches, and Challenges - Orciani, Monia; Fini, Milena; Di Primio, Roberto; Mattioli-Belmonte, Monica (Frontiers in Bioengineering and Biotechnology, 2017)
The growing occurrence of bone disorders and the increase in ageing population have resulted in the need for more effective therapies to meet this request. Bone tissue engineering strategies, by combining biomaterials, cells and signaling factors, are seen as alternatives to conventional bone grafts for repairing or rebuilding bone defects. Indeed, skeletal tissue engineering has not yet achieved full translation into clinical practice because of several challenges. Bone biofabrication by additive manufacturing techniques may represent a possible solution, with its intrinsic capability for accuracy, reproducibility, and customization of scaffolds as well as cell and signaling molecule delivery. This review examines the existing research in bone biofabrication and the appropriate cells and factors selection for successful bone regeneration as well as limitations affecting these approaches.